The Effect of Service Recovery on Customer Satisfaction, eWOM, and Repurchase Intention in the Online Travel Agent (OTA) Industry in Indonesia with Service Failure Severity as Moderator - Gani, Leilani; Fonda, Lie; Prasetyo, Singgih Hadi; Gunadi, Willy (Jurnal Manajemen Teknologi, 2024)
Abstract. This study aims to determine the effect of service recovery on service failure severity, customer satisfaction, eWOM, and repurchase intention. This study adopts an online survey method by distributing 196 online questionnaires to Indonesian OTA users who experienced service failures within the past year. The proposed study model undergoes examination using a partial least square-structural equation model (PLS-SEM). The result reveals that service recovery variables positively and significantly affected customer satisfaction, eWOM, and repurchase intention, however, the severity of the service failure did not significantly impact the relationship between service recovery and customer satisfaction. This study aims to provide valuable insight that enables OTA industry practitioners in Indonesia to develop more effective service recovery strategies. It contributes to developing justice theory and the service failure severity factor as moderators of service failures in the Indonesian OTA industry and their effect on customer satisfaction, eWOM, and repurchase intention. Keywords: Service Recovery, Justice Theory, Online Travel Agent, Service Failure Severity, eWOM, Repurchase Intention Abstrak. Penelitian ini bertujuan untuk melihat pengaruh dari service recovery terhadap variabel service failure severity, customer satisfaction, eWOM dan repurchase intention. Penelitian dilakukan dengan menyebarkan 196 kuesioner menggunakan metode online survey yang melibatkan responden pengguna OTA di Indonesia yang pernah mengalami kegagalan layanan dalam satu tahun terakhir. Pengujian dilakukan atas model penelitian yang diusulkan menggunakan partial least square - structural equation model (PLS-SEM). Hasil penelitian menunjukan bahwa variabel service recovery mempengaruhi customer satisfaction, eWOM, dan juga repurchase intention secara positif dan signifikan, namun variabel service failure severity tidak memiliki pengaruh yang signifikan dalam memoderasi pengaruh dari service recovery terhadap customer satisfaction. Penelitian ini memberikan wawasan bagi manajemen industri OTA di Indonesia dalam merancang strategi service recovery yang efektif. Penelitian ini berkontribusi pada perluasan justice theory dan faktor service failure severity sebagai moderasi terhadap kegagalan layanan di industri OTA di Indonesia serta pengaruhnya terhadap customer satisfaction, eWOM, dan repurchase intention. Katakunci: Service Recovery, Justice Theory, Online Travel Agent, Service Failure Severity, eWOM, Repurchase Intention